2016
DOI: 10.1111/wre.12209
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of six commonly used reference genes for gene expression studies in herbicide‐resistant Avena fatua biotypes

Abstract: Summary Avena fatua of the family Poaceae is one of the most common and economically damaging grass weeds. Resistance to herbicides that inhibit acetyl‐coenzyme A carboxylase and acetolactate synthase activities has recently been detected in A. fatua. The resistance may be due to mutations in the herbicide targets and/or enhanced herbicide metabolism resulting from changes in gene expression, including in genes involved in detoxifying herbicide active ingredients. To analyse gene expression, stable housekeepin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 29 publications
5
30
0
Order By: Relevance
“…This was somewhat consistent with the previous results 18S or 28S is an ideal reference gene for normalisation of qPCR data (Bagnall & Kotze 2010). TBP is as one of the most stably expressed genes in previous study of A. fatua (Wrzesińska et al 2016) as well as the research in Solanum lycopersicum and Lolium multiflorum L. (Expósito-Rodríguez et al 2008;Wang et al 2015). ACT as traditional reference genes is not always stable in different experimental conditions, which was somewhat in accordance with several studies demonstrating ACT as an unsuitable internal control for RT-PCR in other cell types or species (Lord et al 2010).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This was somewhat consistent with the previous results 18S or 28S is an ideal reference gene for normalisation of qPCR data (Bagnall & Kotze 2010). TBP is as one of the most stably expressed genes in previous study of A. fatua (Wrzesińska et al 2016) as well as the research in Solanum lycopersicum and Lolium multiflorum L. (Expósito-Rodríguez et al 2008;Wang et al 2015). ACT as traditional reference genes is not always stable in different experimental conditions, which was somewhat in accordance with several studies demonstrating ACT as an unsuitable internal control for RT-PCR in other cell types or species (Lord et al 2010).…”
Section: Discussionsupporting
confidence: 92%
“…However, some reports indicated 18S was recommended to validate gene expression data in Solanum melongena L. or Oryza sativa L. (Kim et al 2003;Gantasala et al 2013). GAPDH was one of the most stably expressed genes in our results consistent with the previous results in A. fatua (Wrzesińska et al 2016) as well as other weed species, such as Alopecurus myosuroides Huds and Lolium sp. (Duhoux & Délye 2013).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results demonstrated that traditional reference gene ACT, involved in cytoskeleton structure, was not usually unchange under diverse experimental treatments. Similar findings were verified in the beetle Tribolium castaneum [34], perigord black truffle [35] and Avena fatua [36]. Therefore, no reference genes in multiple species show unchanged expression across all the tested conditions [37,38], suggesting that it is of particular important to identify suitable reference genes in BGA.…”
Section: Evaluation Of Reference Genes Expression Stabilitysupporting
confidence: 71%
“…Avena fatua L. (wild oat) is listed among the most common and economically threatening grass weed species of cereal crops all over the world [ 7 – 10 ]. Several traits may account for wild oat’s success as a weed, among them: high competitiveness, multiple herbicide resistance, crop mimicry (similar phenology) and varied germination strategies [ 8 , 11 ].…”
Section: Introductionmentioning
confidence: 99%